2001
DOI: 10.1002/ijc.1367
|View full text |Cite
|
Sign up to set email alerts
|

Tumor heterogeneity in small hepatocellular carcinoma: Analysis of tumor cell proliferation, expression and mutation of p53 AND ?-catenin

Abstract: Most hepatocellular carcinomas (HCCs) first occur as welldifferentiated HCCs, from which poorly differentiated HCC cells develop because of dedifferentiation. In this study, we try to clarify the changes of dedifferentiation and cell proliferative activity and their relationship in small HCCs (less than 3.0 cm in diameter) and try to learn the mechanism of these changes by analysing the expressions and genetic changes of proliferation-related genes p53 and ␤-catenin. Of 41 surgically resected small HCCs, 11 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 25 publications
0
52
1
1
Order By: Relevance
“…Mutations of this gene have been identified in 30%-50% of HCC patients in some geographic areas [19] . An et al [20] reported that there is histological heterogeneity in established HCC, which is accompanied with increased proliferative activity and p53 overexpression. Overexpression of p53 has identified in 37.5% of Japanese HCC patients and 62.5% of Indonesian HCC patients [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of this gene have been identified in 30%-50% of HCC patients in some geographic areas [19] . An et al [20] reported that there is histological heterogeneity in established HCC, which is accompanied with increased proliferative activity and p53 overexpression. Overexpression of p53 has identified in 37.5% of Japanese HCC patients and 62.5% of Indonesian HCC patients [18] .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In some reports, b-catenin overexpression and mutations have been related to early-stage HCCs 19,20 and in others to cancer progression. 21 These data suggest the participation of a WNT/b-catenin pathway in HCC progression, but the involvement of specific components in this pathway remains unclear. A few reports have linked a b-catenin-independent pathway to Wntdependent growth and to the inhibition of apoptosis.…”
mentioning
confidence: 93%
“…However, it has to be noted that xenografts at first passages lose their differentiation degree, show a high level of proliferating activity, and express p53, which in one case was associated with two Tp53 gene mutations. These characteristics reflect mostly an advanced tumor stage and suggest that this model probably selects the more undifferentiated clones that have growth and survival advantages and that can exist even in tumors classified as early stage (35,36). If not resected, these undetectable and undifferentiated clones would progressively evolve into overt cancer, finally leading to a typical advanced stage.…”
Section: Discussionmentioning
confidence: 99%